Automatisierte, minimalinvasive Sicherheitsanalyse und Vorfallreaktion für industrielle Systeme - Patzer, Florian (Karlsruher Schriften zur Anthropomatik, 2022)
Automated defense and prevention measures designed to protect industrial automation and control systems often compromise their real-time processing, resilience and redundancy. Therefore, they need to be performed as non-invasively as possible. Nevertheless, particularly minimally invasive security analysis and incident response are still poorly researched. This work presents solutions based on new semantic- and SDN-based approaches to some of the most important problems in these areas.